Barriers and facilitators of adherence to treatment interventions for COPD amongst individuals from minority ethnic communities: Meta-ethnography - Sarah Alamer; Anna Robinson-Barellla; Matthew Cooper; Hamde Nazar; Andy Husband (PLoS ONE, 2025)
Objective Numerous studies have documented the low adherence rate to treatment interventions for Chronic Obstructive Pulmonary Disease (COPD) amongst minority ethnic communities. This systematic meta-ethnographic review was performed to identify barriers and facilitators of adherence to treatment interventions (e.g., smoking cessation and pulmonary rehabilitation) of COPD in minority ethnic communities. Method This systematic meta-ethnographic review followed the approach by Noblit and Hare. Systematic searches were performed across six databases MEDLINE (OVID), EMBASE (OVID), CINAHL (EBSCO), PsycINFO (OVID), Web of Science, and Scopus from their inception until November 2023. Quality appraisal of included studies was conducted using Critical Appraisal Skills Programme (CASP) tools. Results Out of 1,329 identified citations, seven qualitative studies were included in this meta-ethnography. Using reciprocal translation, four overarching themes were developed to represent the barriers and facilitators of adherence to treatment interventions of COPD amongst minority ethnic communities: 1) positive and negative experiences affecting a person’s motivation for their care, 2) patient attitude and beliefs, 3) being able to access and attend care, and 4) the influence of communication and culture on a person’s care. Conclusion This review highlighted the barriers and facilitators of adherence to treatment interventions for COPD amongst individuals from minority ethnic communities. The key barriers include language difficulties and the inability to comprehend and communicate effectively with healthcare professionals. This demonstrates the need for further research on the impact of linguistic and cultural characteristics on adherence to treatment interventions for COPD. Addressing ethnicity-specific barriers could inform the development of tailored protocols and strategies for optimising adherence among minority ethnic communities. (PROSPERO CRD42023476187).